PERAN PENDAMPING DESA DALAM UPAYA OPTIMALISASI PEMBANGUNAN DESA DI DESA ANGGANA KECAMATAN ANGGANA KABUPATEN KUTAI KARTANEGARA - Artikasari artikasari (ADMINISTRASI PUBLIK, 2020)
ARTIKASARI, Role of Village Facilitators in Efforts to Optimize Village Development in Anggana Village, Anggana District, Kutai Kartanegara Regency. Under the guidance of Mr. Drs. H. Maskan AF, MSI as Counselor I and H. Marsuq, S. Sos, M.Si as Supervisor II.               The purpose of this study is to find out whether there is a Role of Village Facilitators in Efforts to Optimize Village Development in Anggana Village, Anggana District, Kutai Kartanegara Regency. To get the author's data the author conducted the research directly into the field. The results showed that the Village Companion Role in Angana Village, Anggana District, Kutai Kartanegara District was very influential in efforts to optimize the development of the Village in Anggana Village.               In an effort to Optimize Village Development in Anggana Village, Anggana District, Kutai Kartanegara District, the role of Village Facilitators is very much needed and also cooperation from Village Government Officials and Communities so that Village Development can run optimally and smoothly to realize an advanced, independent, prosperous, just and prosperous Village.               The potential of natural resources such as petroleum, giant prawns, the results of rice fields owned by Anggana Village, Anggana District, Kutai Kartanegara Regency is the basic capital to carry out development and improve community welfare.               The role of human resources in implementing development in Anggana Village, Anggana District, Kutai Kartanegara Regency is very much needed and the participation of Village Government Officials and Village Facilitators can encourage the success of development in the Village.The companion role of Anggana Village Anggana Subdistrict, Kutai Kartanegara Regency is very important because the development process in Anggana Village needs assistance from Village Facilitators starting from the planning process, supervision, development process, community economic development and efforts to increase the capacity of Village Government Officials in community empowerment so that development in the Village Anggana Anggana District, Kutai Kartanegara Regency can run optimally and reach its destination.